Mode II fracture of a soft composite gel - Chan, Shau Hua (2019)
This final year project aims to experimentally investigate how various factors including varying inhomogeneity index (varying concentration of multiple layer soft composite gel) of test piece (soft composite gel), varying soft composite gel concentrations, varying initial crack length, specifically on two layered gel test specimen, would influence the initial displacement and force required for first crack initiation, as well as the final displacement and force required for critical failure point.. The study has significant relevance for understanding fracture of soft composite gel materials for example biological materials such as soft tissues found in humans and animals alike. The author will focus on fracture under mode II, in which the loading is in-plane and parallel to the crack face. The primary goal is to determine how inhomogeneity ratio, concentration, as well as initial crack length affects fracture characteristics of soft composite gel. Experimentation, supplemented by simple analysis, will be the main tool for this investigation.